The effect of ink formulation and electrode geometry design on the electrochemical performance of a printed alkaline battery. (1st February 2017) - Saidi, Alireza; Desfontaines, Laurent; Champeval, Alain; Lebreux, Jean-David; Lecomte, Christiane; Pruneau, Michael; Grondein, Aurélie; Izquierdo, Ricardo; Bélanger, Daniel
Abstract: Printed alkaline batteries based on a zinc anode and a manganese dioxide cathode using two different potassium hydroxide-based electrolytes were prepared. Inks were developed for both electrodes and electrolytes to fabricate the batteries by screen-printing techniques. Potentiodynamic electrochemical measurements allowed us to determine the electrochemical utilization of the active components of each electrode ink. Galvanostatic discharge measurements were used to characterize the printed batteries based on optimized ink formulations and to investigate the effect of the cell design. The electrochemical performance of an alkaline printed battery can be significantly improved by proper selection of the components used for the formulation of the ink of each layer of the cell and customizing its design.